PROBLEMATIKA GURU SOSIOLOGI DALAM PELAKSANAAN KURIKULUM MERDEKA DI MAN 2 MATARAM - Izhar Husadi; Ni Made Novi Suryanti; Nursaptini Nursaptini; Masyhuri Masyhuri (Universitas Hamzanwadi, 2025)
The purpose of this study was to explore the challenges faced by sociology teachers in implementing the Independent Curriculum at MAN 2 Mataram. This research employed a qualitative approach using a case study design. Both primary and secondary data were utilized in the study. The main subjects were sociology teachers at MAN 2 Mataram, while additional informants included the Vice Principal for Academic Affairs and the Madrasah Supervisor. Data collection was conducted through interviews, observations, and documentation. The data analysis process followed Creswell’s (2014) qualitative analysis steps: (1) organizing the data, (2) creating memos, (3) describing, categorizing, and interpreting the data into codes and themes, (4) interpreting the data, and (5) presenting and visualizing the findings. The results revealed several issues encountered by sociology teachers in implementing the Independent Curriculum at MAN 2 Mataram. These included: a limited understanding of the core principles of the curriculum, challenges in designing teaching modules, a lack of creativity in selecting appropriate learning models or methods, and a continued reliance on outdated teaching practices.